Design and synthesis of a monocyclic derivative as a selective ACC1 inhibitor by chemical modification of biphenyl ACC1/2 dual inhibitors. (1st April 2021) - Mizojiri, Ryo; Tomita, Daisuke; Sasaki, Masako; Satoh, Yoshihiko; Yamamoto, Yukiko; Sumi, Hiroyuki; Maezaki, Hironobu
Graphical abstract: Abstract: A structure–activity relationship (SAR) study towards novel ACC1-selective inhibitors was carried out by modifying the molecular length of the linker in biaryl derivative 1 g, an ACC1/2 dual inhibitor. Ultimately, this leads us to discover novel phenoxybenzyloxy derivative 1i as a potent ACC1-selective inhibitor. Further chemical modification of this scaffold to improve cellular potency as well as physicochemical and pharmacokinetic (PK) properties produced N -2-(pyridin-2-ylethyl)acetamide derivative 1n, which showed highly potent ACC1-selective inhibition as well as sufficient PK profile for further in vivo evaluations. Oral administration of 1n significantly reduced the concentration of malonyl-CoA in HCT-116 xenograft tumors at doses of 100 mg/kg. Accordingly, our novel series of potent ACC1-selective inhibitors represents a set of useful orally-available research tools, as well as potential therapeutic agents for cancer and fatty acid-related diseases.